Artificial Immune Systems Applied to the Analysis of Structural Integrity of a Building - Anjos Lima, Fernando Parra dos [UNESP]; Chavarette, Fabio Roberto; Frutuoso de Souza, Simone Silva; Santos e Souza, Adriano dos [UNESP]; Martins Lopes, Mara Lucia; Wang, Y. (Trans Tech Publications Ltd, 2014)
This paper presents the application of artificial immune systems for analysis of the structural integrity of a building. Inspired by a biological process, it uses the negative selection algorithm to perform the identification and characterization of structural failure. This paper presents the application of artificial immune systems for analysis of the structural integrity of a building. Inspired by a biological process, it uses the negative selection algorithm to perform the identification and characterization of structural failure. This methodology can assist professionals in the inspection of mechanical and civil structures, to identify and characterize flaws, in order to perform preventative maintenance to ensure the integrity of the structure and decision-making. In order to evaluate the methodology was made modeling a two-story building and several situations were simulated (base-line condition and improper conditions), yielding a database of signs, which were used as input data for the negative selection algorithm. The results obtained by the present method efficiency, robustness and accuracy.
Keywords: Analysis of Structural Integrity; Building; Artificial Immune Systems; Negative Selection Algorithm